Efeitos do método Mckenzie e da estabilização em idosos com dor lombar crônica - Correia, Camilla Ferreira (2019)
Introduction: Chronic low back pain is one of the most relevant health conditions among the elderly and its prevalence estimate is higher than other musculoskeletal conditions. The McKenzie method and Stabilization are widely used in the treatment of adults with chronic low back pain, however it is a subject that needs further studies in order to analyze the efficacy of these therapies in the elderly. Objectives: To verify the effects of Stabilization and the McKenzie method in the treatment of chronic low back pain in the elderly. Methods: A randomized double blind study was performed with 11 elderly patients randomly divided into two groups: (A) Stabilization and (B) McKenzie. All were submitted to pain evaluation and functional performance. Each group received 10 appointments lasting 50 minutes, 2 days a week, for 5 weeks. The volunteers were evaluated before, during and after the end of the interventions. Results: Group (A) only showed significant difference for functionality (p <0.05), whereas (B) did not have significant difference in pain and functionality items (p> 0.05). Conclusion: When considering the structural and physiological changes that occur in the elderly, there is a need for studies that use both techniques with this population, as well as in a larger sample.